Remediation of Soil Contaminated with Heavy Metals - Plyatsuk L. D.; Chernysh Y. Y.; Ablieieva I. Y.; Yakhnenko O. M.; Bataltsev E. V.; Balintova M.; Hurets L. L. (Журнал інженерних наук)
The paper is focused on the research of the applied aspects of soil remediation, in particular the process of heavy metals (HM) binding and intensifying the cultivation of a soil microbiome using various organic-mineral compositions: biogenic composite, which is the product of anaerobic transformation of sewage sludge and phosphogypsum; organic-mineral compost, based on a mixture of phosphogypsum, superphosphate and cattle humus; and a combination of a mixture of sodium humate and superphosphate. The integration of theoretical and experimental principles in the synergy analysis of the interrelations in the system “object – subject of research” in the study of the dynamics of changes in the forms of HM finding in the soil was carried out. The percentage content of the mobile forms of HM released by the extractant from their gross content before and after the treatment of the soil with organic-mineral compositions was determined with the spectrophotometric method using. The comparison of the soil processing efficiency was determined. Correlation relations of the dynamics in the biomass oxidative ability values for the soil biome and the rate of the substrate oxidation was proved over time treatment with different doses of the biocomposite with using of mathematical statistics methods.